Integration Model of Navigation and Port Information Systems with Blockchain Technology to Enhance Ship Operational Reliability - Chanra Purnama; Larsen Barasa; Denny Fitrial (International Journal of Mechanical, Industrial and Control Systems Engineering, 2026)
This research investigates integration models combining navigation and port information systems through blockchain technology to enhance ship operational reliability, addressing critical challenges in data integrity, information sharing, and system coordination affecting maritime operations. Current maritime information systems operate in silos with limited interoperability, creating information asymmetries, coordination inefficiencies, and data integrity concerns that compromise operational decision-making and safety management. Through qualitative analysis involving ship operators, port authorities, navigation system providers, blockchain specialists, and maritime regulators, this study examines how distributed ledger technology can enable secure, transparent, and tamper-proof information integration across navigation and port systems. Results demonstrate that blockchain-based integration can improve data integrity assurance by 70-90%, reduce coordination time by 40-60%, enhance operational transparency by 55-75%, and decrease documentation errors by 50-70% through immutable records, smart contracts, and decentralized consensus mechanisms. Key implementation challenges include technical complexity, computational requirements, regulatory uncertainty, organizational adoption resistance, and scalability limitations. Findings reveal that blockchain represents transformative enabling technology for maritime digital ecosystems requiring trusted information exchange among multiple stakeholders without centralized intermediaries. This research contributes to maritime information systems literature by providing practical frameworks for blockchain implementation supporting operational reliability enhancement.